High frequency of Plasmodium falciparum chloroquine resistance marker (pfcrt T76 mutation) in Yemen: An urgent need to re-examine malaria drug policy - Al-Mekhlafi, A.M.; Mahdy, M.A.K.; Al-Mekhlafi, H.M.; Azazy, A.A.; Fong, Mun Yik (BMC, 2011)
Background: Malaria remains a significant health problem in Yemen with Plasmodium falciparum being the predominant species which is responsible for 90 of the malaria cases. Despite serious concerns regarding increasing drug resistance, chloroquine is still used for the prevention and treatment of malaria in Yemen. This study was carried out to determine the prevalence of choloroquine resistance (CQR) of P. falciparum isolated from Yemen based on the pfcrt T76 mutation. Methods: A cross-sectional study was carried out among 511 participants from four governorates in Yemen. Blood samples were screened using microscopic and species-specific nested PCR based on the 18S rRNA gene to detect and identify Plasmodium species. Blood samples positive for P. falciparum were used for detecting the pfcrt T76 mutation using nested-PCR. Results: The prevalence of pfcrt T76 mutation was 81.5 (66 of 81 isolates). Coastal areas/foothills had higher prevalence of pfcrt T76 mutation compared to highland areas (90.5 vs 71.8) (p = 0.031). The pfcrt T76 mutation had a significant association with parasitaemia (p = 0.045). Univariate analysis shows a significant association of pfcrt T76 mutation with people aged > 10 years (OR = 9, 95 CI = 2.3 - 36.2, p = 0.001), low household income (OR = 5, 95 CI = 1.3 - 19.5, p = 0.027), no insecticide spray (OR = 3.7, 95 CI = 1.16 - 11.86, p = 0.025) and not sleeping under insecticide treated nets (ITNs) (OR = 4.8, 95 CI = 1.38 - 16.78, p = 0.01). Logistic regression model confirmed age > 10 years and low household income as predictors of pfcrt T76 mutation in Yemen P. falciparum isolates. Conclusions: The high prevalence of pfcrt T76 mutation in Yemen could be a predictive marker for the prevalence of P. falciparum CQR. This finding shows the necessity for an in-vivo therapeutic efficacy test for CQ. P. falciparum CQR should be addressed in the national strategy to control malaria.